2021
DOI: 10.21037/atm-21-196
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of hybrid ablation for persistent and longstanding persistent atrial fibrillation

Abstract: Atrial fibrillation is the most common sustained arrhythmia and is characterized by rapid and irregular atrial activation with loss of atrial contraction. There has been a significant evolution of treatments over the past 30 years. Initially, cardiac surgeons developed approaches via sternotomy with superior efficacy, however early iterations of the procedure were associated with prolonged recovery time and frequent need for pacemaker placement. The current surgical approach to the maze procedure via sternotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…For persistent and longstanding persistent AF (>1 year), the recommendations are IIa, and IIb respectively. For persistent or long-standing persistent AF, posterior wall isolation and ablation of non PV triggers also has a Class IIb recommendation (92).…”
Section: Direct Comparisons Of Surgical and Catheter Ablation Of Afmentioning
confidence: 99%
See 2 more Smart Citations
“…For persistent and longstanding persistent AF (>1 year), the recommendations are IIa, and IIb respectively. For persistent or long-standing persistent AF, posterior wall isolation and ablation of non PV triggers also has a Class IIb recommendation (92).…”
Section: Direct Comparisons Of Surgical and Catheter Ablation Of Afmentioning
confidence: 99%
“…As noted above, hybrid ablation studies have plagued by lack of uniformity in approaches, lesion sets, catheter ablation timing relative to the surgical approach, and follow-up protocols (92).…”
Section: Hybrid Af Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Over the past 30 years, there has been an exponential growth in the clinical treatment of AF including drug treatment (anticoagulation, heart rate control, and rhythm control), cardioversion, cardiac ablation, and other interventional procedures. 1,6,7 In accordance with the guideline of the National Institute for Health and Care Excellence (NICE), radiofrequency (RF) ablation is suitable for symptomatic paroxysmal or persistent AF patients if drug treatment is unsuccessful, unsuitable, or intolerable. 8 With the rapid increase of AF ablation procedures in recent years, the operators meet some challenges such as transseptal puncture, anatomic variation of pulmonary veins, and risk of esophageal injury.…”
Section: Introductionmentioning
confidence: 99%
“…AF prevalence increases with age and it is reported that the lifetime risk of AF is about 37% after 55 years old 3–5 . Over the past 30 years, there has been an exponential growth in the clinical treatment of AF including drug treatment (anticoagulation, heart rate control, and rhythm control), cardioversion, cardiac ablation, and other interventional procedures 1,6,7 . In accordance with the guideline of the National Institute for Health and Care Excellence (NICE), radiofrequency (RF) ablation is suitable for symptomatic paroxysmal or persistent AF patients if drug treatment is unsuccessful, unsuitable, or intolerable 8…”
Section: Introductionmentioning
confidence: 99%